Mushaf Blawong Gogodalem: Interpretasi Sejarah Melalui Pendekatan Kodikologi - Nor Lutfi Fais; Abdul Jamil; Sukendar Sukendar (Lajnah Pentashihan Mushaf Al-Qur'an, 2022)
This study focuses on four Quranic manuscripts located in Gogodalem. According to local beliefs, the manuscripts were written by Mbah Jamaluddin. However, preliminary study shows that the four manuscripts cannot be attributed to Mbah Jamaluddin. The use of manuscript paper that is not found chain line along the vertical line of the paper indicates that the manuscript came from the early 19th century. In addition, the existing style of authorship also indicates that all manuscripts were written by more than one person. Through codicological and historical approaches, this study seeks to provide a historical interpretation of Gogodalem’s manuscripts. The result found that the four manuscripts had a relationship with the Surakarta Palace. This interpretation is based on the use of the manuscript paper, the illumination model, and the historical relationships it has. Meanwhile, the description of the manuscript shows that the rasm used is a mixture of usmani and imla̅'i̅, and followed qiraat of Imam Hafṣ. It used also a simple and inconspicuous model of floral illumination.